Childbearing and risk of cataract in young women: an epidemiological study in central India. Issue 5 (1st May 2002) - Minassian, D C; Mehra, V; Reidy, A
Abstract : AUTHOR:e-mail address please Background/aims: Observations in central India, over a period of more than a decade, suggested that the frequency of sight restoring cataract surgery was substantially higher in women of childbearing age compared to men of the same age. Formal surveys in the subcontinent of India have confirmed a higher prevalence of cataract in women. The present study was conducted to explore possible effects of childbearing and associated adverse factors on cataract risk. Methods: A case-control study design was used. Cases were mothers aged 35–45 with bilateral "senile" cataract. Controls were mothers of the same age but with clear lenses, attending the hospital services with other, mostly minor, complaints. Results: A significant association was found between childbearing and risk of sight impairing cataract in mothers. Having more than three babies doubled the risk (adjusted odds ratio 2.0, p=0.012), and the risk increased by an estimated 20% for each additional birth. The birth effect was independent of age, socioeconomic status (occupation and income level), body mass index, and multiple episodes of severe dehydration, all regarded as putative risk factors for cataract. Conclusions: Having more than three babies may substantially increase the risk of sight impairing cataract in mothers of childbearing age in central India. The findings open new research challenges to identify cataract risk factors to which mothers may be exposed during pregnancy and childbirth, particularly under poor socioeconomic conditions.